A Study of Metabolic Syndrome Parameters in Post Graduate Students in Dr. B. R. Ambedkar Medical College Hospital - Omar Shariff, Mohamed; Supriyaa, B. B.; Bhakthavatchalam, N. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Metabolic syndrome is a clustering of risk factors that increase an individual’s probability of developing atherosclerotic cardiovascular disease, Type 2 diabetes mellitus and all-cause mortality. It is considered as a major public health concern since the prevalence has reached epidemic proportions in the past decade and ever increasing. Concern were raised regarding increasing prevalence among students community. The study was conducted on 60 patients in the Department of General medicine at DR. B. R. Ambedkar Medical College Hospital, Bengaluru. It was a hospital based prospective study from October 2018 to October 2019. Informed consent was obtained from all participants who were included to be for the study. Detailed history was obtained from patients and subjected for clinical examination, biochemical test. The aim was to estimate the prevalence of the metabolic syndrome in postgraduate students in Dr. B R Ambedkar Medical College Hospital, Bangalore. Metabolic syndrome is a clustering of risk factors that increase an individual’s probability of developing atherosclerotic cardiovascular disease, Type 2 diabetes mellitus and all-cause mortality. It is considered as a major public health concern since the prevalence has reached epidemic proportions in the past decade and ever increasing. Occurrence of metabolic syndrome in a given individual confers a 5-fold increase in the risk of Type 2 Diabetes Mellitus (DM) (1).Metabolic syndrome is a clustering of risk factors that increase an individual’s probability of developing atherosclerotic cardiovascular disease, Type 2 diabetes mellitus and all-cause mortality. It is considered as a major public health concern since the prevalence has reached epidemic proportions in the past decade and ever increasing. Concern were raised regarding increasing prevalence among students community. The study was conducted on 60 patients in the Department of General medicine at DR. B. R. Ambedkar Medical College Hospital, Bengaluru. It was a hospital based prospective study from October 2018 to October 2019. Informed consent was obtained from all participants who were included to be for the study. Detailed history was obtained from patients and subjected for clinical examination, biochemical test. The aim was to estimate the prevalence of the metabolic syndrome in postgraduate students in Dr. B R Ambedkar Medical College Hospital, Bangalore. Metabolic syndrome is a clustering of risk factors that increase an individual’s probability of developing atherosclerotic cardiovascular disease, Type 2 diabetes mellitus and all-cause mortality. It is considered as a major public health concern since the prevalence has reached epidemic proportions in the past decade and ever increasing. Occurrence of metabolic syndrome in a given individual confers a 5-fold increase in the risk of Type 2 Diabetes Mellitus (DM) (1).
Keywords: Metabolic syndrome; Diabetes mellitus; Hypertension